BEYOND LIVE STREAMING: HOW IMMERSION AND CONSUMER TRUST SHAPE PURCHASE INTENTION IN TIKTOK LIVE COMMERCE - Muhammad Yasser Iqbal Daulay; Islamuddin (Universitas Muhammadiyah Bengkulu, 2026)
Live-streaming commerce has become a major component of social commerce, particularly on platforms such as TikTok that combine real-time interaction with online shopping. This study examines the effect of live streaming on purchase intention by considering the mediating roles of immersion and consumer trust. Based on the Stimulus–Organism–Response (SOR) framework and Flow Theory, the research explores how live-streaming experiences influence consumers’ psychological responses and behavioral intentions. A quantitative approach was applied using survey data from 229 TikTok users who had watched live-streaming sessions featuring fashion products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that both immersion and consumer trust positively and significantly influence purchase intention, with consumer trust exerting a stronger effect. However, live streaming does not significantly affect immersion, consumer trust, or purchase intention. These results suggest that internal psychological factors, particularly trust and immersion, play a more important role than technological features in shaping consumer purchase intentions in live-streaming commerce